2012
DOI: 10.1590/s1516-35982012000900002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity based on morphological data in Panicum maximum hybrids

Abstract: -The objective of this experiment was to evaluate the genetic divergence between hybrids obtained from 10 sexual genitors of the Panicum maximum breeding program at Embrapa Beef Cattle. For this, the following morphological descriptors were used: plant height, growth habit, leaf aspect, leaf waxiness, hair density on the sheath (DePB) and blade (DePL), degree of hardiness of the hairs on the leaf sheath (DuPB) and blade (DuPL) and length of hairs on the sheath and blade. The characteristics growth habit and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Studies of morphological variation in plants are a useful tool in genetic improvement programs and enable access to the genetic variability within a germplasm bank (Azevedo et al 2011;Martuscello et al, 2012). In plant breeding programs, knowledge of variability and genetic diversity within a species is essential for the rational use of genetic resources (Govindaraj et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of morphological variation in plants are a useful tool in genetic improvement programs and enable access to the genetic variability within a germplasm bank (Azevedo et al 2011;Martuscello et al, 2012). In plant breeding programs, knowledge of variability and genetic diversity within a species is essential for the rational use of genetic resources (Govindaraj et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Brasil apresenta cerca de 172 milhões de hectares de pastagens, que correspondem a quase 22% de seu território (Martuscello et al 2012). Aproximadamente 90% dos nutrientes consumidos pelos ruminantes são originados a partir de plantas forrageiras (euclides et al 2010).…”
Section: _____________________________________unclassified
“…For example, Tuhina-Khatunm et al (2015) show the importance of determining genetic variation based on morphological traits. Recent articles published by Martuscello et al (2012), Pereira et al (2012), Rocha et al (2017) and Kaur et al (2018) showed the importance of genetic variability and detected high variability in forage species based on zootechnical traits. In this way, some biometric strategies, including data processing using principal component analysis, principal coordinate analysis, and group structure approaches, stand out as useful options for understanding trait relationships in a population.…”
Section: Introductionmentioning
confidence: 99%